AACC Guidance Document on Laboratory Testing for the Assessment of Preterm Delivery. (2nd June 2021) - Farnsworth, Christopher; Schuler, Erin E; Woodworth, Alison; Straseski, Joely; Pschirrer, E Rebecca; Nerenz, Robert D
Abstract: Identifying women with preterm labor who will go on to deliver prematurely is crucial to improving outcomes for mother and baby and for saving healthcare resources. Even among those with symptoms, the number of women who deliver preterm is low, and thus the low positive predictive value (PPV) and high negative predictive value (NPV) associated with available biomarkers does not substantially reduce the uncertainty of the clinical diagnosis. While there is some promise in the use of fetal fibronectin (fFN), interleukin 6 (IL-6), or placental alpha microglobulin 1 (PAMG-1) for predicting preterm birth (PTB), their use is unlikely to provide considerable clinical value in populations with a low prevalence. To provide real clinical benefit, a biomarker must demonstrate a high PPV to allow identification of the minority of symptomatic women who will deliver prematurely. As none of the currently available biomarkers exhibit this performance characteristic, we do not recommend their routine clinical use in populations with a pre-test probability of PTB of <5%. Limiting biomarker testing to only high-risk women identified on the basis of cervical length or other characteristics will increase the pre-testprobability in the tested population, thereby improving PPV. PAMG-1 is associated with a higher PPV than fFN and may show clinical utility in populations with a higher pre-test probability, but further work is required to conclusively demonstrate improved outcomes in this patient group.